Eco-Centric Resource Management Practices in Farming and Food Industries (Emerging Indexing of Global Multidisciplinary Journal, 2026)
Eco-centric resource management has emerged as a transformative paradigm in the farming and food industries, shifting focus from production maximization to ecological balance, resource efficiency, and sustainability. Conventional agricultural and food processing systems, characterized by linear resource use and environmental externalities, have led to resource depletion, ecological degradation, and inefficiencies across supply chains. In response, eco-centric models emphasize circular resource flows, technological integration, and ecosystem-oriented decision-making.This study critically examines the theoretical foundations, technological enablers, and operational frameworks underpinning eco-centric resource management in agriculture and food industries. The research adopts a qualitative synthesis approach, utilizing selected literature on circular economy, vertical farming, Industry 4.0 technologies, and smart agricultural systems. The analysis integrates ecological sustainability principles with advanced technological innovations such as Internet of Things (IoT), robotics, and automation to develop a comprehensive framework for resource optimization.Findings indicate that eco-centric practices—particularly circular economy integration—significantly enhance resource efficiency by reducing waste, optimizing input use, and promoting closed-loop systems (Agarwal et al., 2025). Vertical farming and controlled environment agriculture demonstrate the potential to minimize land and water usage while increasing productivity (Al-Kodmany, 2018; SharathKumar et al., 2020). Furthermore, Industry 4.0 technologies enable real-time monitoring, predictive analytics, and precision resource allocation, thereby improving operational efficiency across the food value chain (Khanna and Kaur, 2019; Duong et al., 2020).However, the study also identifies critical challenges, including high initial investment costs, technological complexity, and limited scalability in developing regions. Institutional constraints and knowledge gaps further hinder widespread adoption. The research highlights the need for integrated policy frameworks, capacity-building initiatives, and technological standardization to facilitate the transition toward eco-centric systems.This paper contributes to the academic discourse by proposing a multidimensional framework that aligns ecological sustainability with technological innovation in resource management. It underscores the importance of transitioning from linear to circular and intelligent systems to achieve long-term sustainability in farming and food industries.